2019
DOI: 10.1101/789529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Landmark-Based Navigation Instructions Improve Incidental Spatial Knowledge Acquisition in Real-World Environments

Abstract: Background. The repeated use of navigation assistance systems leads to decreased spatial orienting abilities. Previous studies demonstrated that augmentation of landmarks using auditory navigation instructions can improve incidental spatial learning when driving on a single route through an unfamiliar environment.Objective. Based on these results, a series of experiments was conducted to further investigate both the impairment of spatial knowledge acquisition by standard navigation instructions and the positiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…All had normal or corrected to normal vision and gave informed consent prior to the study which was approved by the local research ethics committee of the Institute for Psychology and Ergonomics at the Technische Universität (TU) Berlin. Before the main experiment, participants filled out an online questionnaire to determine if they were familiar with the area where the navigation task would take place (Wunderlich & Gramann, 2020). After navigating the route, participants were again asked whether they had been familiar with the navigated route.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…All had normal or corrected to normal vision and gave informed consent prior to the study which was approved by the local research ethics committee of the Institute for Psychology and Ergonomics at the Technische Universität (TU) Berlin. Before the main experiment, participants filled out an online questionnaire to determine if they were familiar with the area where the navigation task would take place (Wunderlich & Gramann, 2020). After navigating the route, participants were again asked whether they had been familiar with the navigated route.…”
Section: Participantsmentioning
confidence: 99%
“…These studies further demonstrated the successful incidental acquisition of landmark and route knowledge when landmark-based rather than standard instructions were used. The experimental setups in these studies ranged from simulated driving through a virtual world (Wunderlich & Gramann, 2018) to interactive videos of walking or actually walking through the real-world (Wunderlich & Gramann, 2020). The results revealed higher amplitudes of the event-related late positive component (LPC) at parietal leads with the cued recall of landmark pictures.…”
mentioning
confidence: 99%
“…All had normal or corrected to normal vision and gave informed consent prior to the study which was approved by the local research ethics committee of the Institute for Psychology and Ergonomics at the Technische Universität (TU) Berlin. Before the main experiment, participants filled out an online questionnaire to determine if they were familiar with the area where the navigation task would take place as used in Wunderlich and Gramann (2020). After navigating the route, participants were again asked whether they had been familiar with the navigated route.…”
Section: Methodsmentioning
confidence: 99%
“…These studies further demonstrated the successful incidental acquisition of landmark and route knowledge when landmark-based rather than standard instructions were used. The experimental setups in these studies ranged from simulated driving through a virtual world Wunderlich and Gramann (2018) to interactive videos of walking through the real world or actual walking through the real-world (Wunderlich and Gramann, 2020). The results of Wunderlich and Gramann (2018) further showed changes in the event-related brain activity with cued recall of landmark pictures, which corresponded to the performance differences observed (Wunderlich and Gramann, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…implemented a microphone and a dedicated processing pipeline to detect the onset of natural sounds and lock the associated EEG analyses to unveil auditory attention processes. In a series of studies looking at spatial knowledge acquisition in natural environments (Wunderlich and Gramann, 2021), the experimenter was following the participants navigating through a urban environment and encoded the timing of experimental events manually through a smartphone interface that was synchronized to the EEG system. These manually encoded timestamps, although arguably not of the highest temporal precision, provide nevertheless a basis for the extraction of experimental events.…”
Section: Capturing Cognitive Events In the Real-worldmentioning
confidence: 99%